Immersive Mixed Reality for Manufacturing Training - Gonzalez-Franco, Mar; Pizarro, Rodrigo; Cermeron, Julio; Li, Katie; Thorn, Jacob; Hutabarat, Windo; Tiwari, Ashutosh; Bermell-Garcia, Pablo (Frontiers in Robotics and AI, 2017)
In the complex manufacturing sector a considerable amount of resources is focused on training workers and developing new skills. Increasing the effectiveness of those processes and reducing the investment required is an outstanding issue. In this paper, we present an experiment (n=20) that shows how modern metaphors such as collaborative Mixed Reality can be used to transmit procedural knowledge and could eventually replace other forms of face-to-face training. We implemented a Mixed Reality setup with see-through cameras attached to a Head Mounted Display. The setup allowed for real-time collaborative interactions and could simulate conventional forms of training. We tested the system implementing a manufacturing procedure of an aircraft maintenance door. The obtained results indicate that performance levels in the Immersive Mixed Reality training were not significantly different than in the conventional face-to-face training condition. These results and their implications for future training and the use of Virtual Reality, Mixed Reality and Augmented Reality paradigms in this context are discussed in this paper.